Dvārakānātha Gaṅgopādhyāẏa - Bāndyopādhyāẏa, Brajendranātha (Baṅgīya-Sāhitya-Pariṣad, 1950)
Inhalt: Kurzbiographie d. bengalischen Sozialreformers Dvārakānātha Gaṅgopādhyāẏa (1844-1898)
Keywords: Biografie